Tomorrow at work: The age of shortages - Ekkehard Ernst; Lisa Feist (Intereconomics, 2024)
This paper examines the effect of the anti-ESG regulations approved in 18 states from 2021 to 2023. Focusing on the fuel energy sector, we find that the regulatory intervention leads to 0.8 % to 3.5 % cumulative abnormal stock returns (CARs) around the regulation approval dates. The market reactions are found to be more positive and pronounced when the firm has poor previous ESG performance, when the firm is financially more constrained, and when the regulation is less controversial. Meanwhile, although fuel energy firms have more institutional ownership afterwards, their carbon emission also increases, indicating potential negative economic effects of anti-ESG policies.After decades marked by struggles to combat high unemployment, today's main challenge is labour market shortages. Since the aftermath of the COVID-19 pandemic and despite the economic slowdown driven by Russia's invasion of Ukraine, EU labour markets have demonstrated remarkable resilience. Employment reached a record high in 2022 and the trend is expected to continue. Most companies, in the EU and beyond, are now struggling to fill vacancies. Labour and skill shortages in several sectors are the new problems to overcome. What are the reasons behind these shortages? Are these only temporary issues? Has unemployment ceased to be a burning issue? What policy options could address these challenges? Based on their presentations at the 2024 edition of the Centre for European Policy Studies, flagship conference, Ideas Lab, the contributors to this Forum attempt to answer these question, discussing recent shifts in the labour market and policy solutions to address the different sources of shortages.
Keywords: J11; J21; J22; J24; 330; Labor shortage; OECD countries; Arbeitskräftemangel; OECD-Staaten